El Salvador Financial Sector Assessment Program Development Module : Capital Markets - World Bank (World Bank, Washington, DC, 2017)
This technical note was prepared in the context of a World Bank Financial Sector Assessment Program mission in the Republic of El Salvador in March 2016. The capital markets in El Salvador continue to remain relatively small but have played a larger role in financing real sector needs in the last 5 years. The investor base is dominated by institutional investors. Two pension funds represent the primary investors in the securities market, followed by banks and insurance companies. The integration with Panama is a welcome development and will help improve opportunities for Salvadoran investors and issuers. The regulation and supervision of capital markets is shared, respectively, between the Central Bank (BCR) and the Financial Superintendency (SSF) and this required stronger coordination. The document contains technical analysis and detailed information underpinning the FSAP assessment’s findings and recommendations. Further information on the FSAP program can be found at www.worldbank.org/fsap.